PERAN BAPPELITBANGDA DALAM MENDORONG INOVASI DAN PENGEMBANGAN EKONOMI LOKAL DI KOTA BANJAR: Peran BAPPELITBANGDA Pasca COVID-19 - Puji Astuti; Farizan, Akmal; Muhammad Naufa Azhayr; Eva Charena Aditiya; Irfan Nursetiawan (Jurnalika : Jurnal Ilmu Komunikasi, 2024)
In March 2020, Indonesia was shocked by a terrible virus, the Covid-19 pandemic. Until August, Covid-19 in Indonesia reached 165,887 including 7,169 deaths covering 34 provinces. Then the Covid-19 outbreak has an impact on the decline in the economic activities of MSMEs in Indonesia, especially Banjar City. The purpose of this research is to find out about how the role of the Regional Planning, Research, Development Agency (BAPPELITBANGDA) when formulating Technical Policies in the Field of Regional Development Research Planning in Banjar City and the factors that affect the economy in Banjar City caused by Covid-19 and improve economic development innovations in Banjar City. The people of Kota Banjar are unable to carry out their usual activities due to the appeal from the government which has set a policy for WFH (Work from Home) and Social Distancing. Therefore, BAPPELITBANGDA drafted an innovation that will be developed gradually which is expected to overcome the decline in the economy in Banjar City. This research uses direct observation techniques using the interview method, the researcher visits the place under study and the researcher obtains other sources through the official website of BAPPELITBANGDA as a source of research data that supports observation.